RETROSPECTIVE ANALYSIS OF THE CONTENT OF TEACHING UKRAINIAN LANGUAGE FOR PROFESSIONAL PURPOSES - Humeniuk, Iryna (Mountain School of Ukrainian Carpaty, 2020)
The article analyses the evolutionary aspects of development of the content of the educational discipline “Ukrainian Language for Professional Purposes”. The aim of the publication is detection of the main tendencies of formation of the content of this discipline in the retrospective vector. A set of methods has been used in the research process: theoretical (analysis and systematization of legislative acts and literary sources for clarification of the degree of solving the issue in the modern scientific area and its legal status), statistical and descriptive methods (for detection of structure changes in the content of the course), methods of visualization and generalization (for comparative analysis of evolutionary changes in the content of the analysed discipline). The author has investigated the stages of formation and development of the educational course “Ukrainian Language for Professional Purposes” from the moment of its appearance in 1989 until now. All changes in the structure and content have legislative accompaniment and substantiation. The main teaching programmes and textbooks of the course have been analysed. Along with highlighting the specificity of the first educational programmes, there have been shown the main difficulties of their implementation. The evolutionary aspects of the content of the discipline “Ukrainian Language for Professional Purposes” have shown themselves by directing it towards formation of a linguistic personality with a set of knowledge, abilities and skills for optimal language behaviour in professional sphere. Linguistic knowledge obtained at school could be generalized and systemized in professional context, but without duplication. According to the stages of development of the educational discipline, the main concepts of its formation, development of its content and the model of alternative courses have been analysed. On the basis of it, comparative characteristics of the content of teaching the courses “Business Ukrainian Language” and “Ukrainian Language for Professional Purposes” have been conducted. Approval of the discipline “Ukrainian Language for Professional Purposes” as a compulsory one had provided wider opportunities for Ukrainian language education of students of all specialities. However, in 2014 the status was changed. This created obstacles for linguistic and communicative education of non-philologist students and caused a new wave of scientific discussion.